Socio-cultural and economic barriers, and facilitators influencing men’s involvement in antenatal care including HIV testing: a qualitative study from urban Blantyre, Malawi - Doreen Sakala; Moses K. Kumwenda; Donaldson F. Conserve; Bassey Ebenso; Augustine T. Choko (BMC Public Health, 2021)
Abstract Background Male partner involvement in antenatal care (ANC) is associated with positive maternal and neonatal outcomes. However, only a handful of men attend ANC with their partners. This study aimed to understand the underlying barriers and facilitators influencing men’s ANC attendance including HIV testing in Blantyre, Malawi. Methods Data were collected during a formative qualitative study of a cluster-randomised trial. Six focus group discussions (FGDs) with 42 men and women and 20 in-depth interviews (IDIs) were conducted at three primary health centres in urban Blantyre, Malawi. FGD participants were purposively sampled with IDI participants subsequently sampled after FGD participation. Thematic analysis was used to analyse the data. Results The economic requirement to provide for their families exerted pressure on men and often negatively affected their decision to attend ANC together with their pregnant partners despite obvious benefits. Peer pressure and the fear to be seen by peers queueing for services at ANC, an environment traditionally viewed as a space for women and children made men feel treated as trespassers and with some level of hostility rendering them feeling emasculated when they attend ANC. Health system problems associated with overall organization of the ANC services, which favours women created resistance among men to be involved. An association between ANC and HIV testing services discouraged men from attending ANC because of their fear of testing HIV-positive in the presence of their partners. The availability of a male friendly clinic offering a private, quick, supportive/sensitive and flexible service was considered to be an important incentive that would facilitate men’s ANC attendance. Men described compensation to cover transport and opportunity cost for attending the clinic as a motivator to attending ANC services and accepting an HIV test. Conclusion Peer and economic influences were the most influential barriers of men attending ANC and testing for HIV with their pregnant partners. Addressing these socio-economic barriers and having a male friendly clinic are promising interventions to promote male ANC attendance in this setting.